2015
DOI: 10.1126/science.aaa2628
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretory granules control autophagy in pancreatic β cells

Abstract: Pancreatic β cells lower insulin release in response to nutrient depletion. The question of whether starved β cells induce macroautophagy, a predominant mechanism maintaining energy homeostasis, remains poorly explored. We found that, in contrast to many mammalian cells, macroautophagy in pancreatic β cells was suppressed upon starvation. Instead, starved β cells induced lysosomal degradation of nascent secretory insulin granules, which was controlled by protein kinase D (PKD), a key player in secretory granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 36 publications
8
148
0
1
Order By: Relevance
“…Previous work describing such structures has identified them as autolysosomes, which are autophagosomes after fusion with lysosomes (Klionsky et al, 2014). In the context of INS-1E cells, these structures are likely involved in degrading vesicle content including insulin and may therefore act as a regulatory control for insulin secretion, though they were not clearly surrounded by two membranes as expected for autophagosomes (Goginashvili et al, 2015, Marsh et al, 2007, Liu et al, 2015). The lysed vesicles and probable autolysosomes may have formed here simply because of the unnaturally high levels of CgA expression following transfection.…”
Section: Discussionmentioning
confidence: 94%
“…Previous work describing such structures has identified them as autolysosomes, which are autophagosomes after fusion with lysosomes (Klionsky et al, 2014). In the context of INS-1E cells, these structures are likely involved in degrading vesicle content including insulin and may therefore act as a regulatory control for insulin secretion, though they were not clearly surrounded by two membranes as expected for autophagosomes (Goginashvili et al, 2015, Marsh et al, 2007, Liu et al, 2015). The lysed vesicles and probable autolysosomes may have formed here simply because of the unnaturally high levels of CgA expression following transfection.…”
Section: Discussionmentioning
confidence: 94%
“…The absence of glucose elevation because of fasting until noon may diminish b-cell responsiveness and memory, leading to a reduced and delayed insulin response after lunch and dinner on the NoB day. Indeed, a recent study reported that lower insulin release by b-cells in response to nutrient depletion or starvation induces lysosomal degradation of nascent secretory insulin granules and that this is controlled by protein kinase D, a key player in secretory granule biogenesis (23). The recovery of the responsiveness of the b-cell's secretory function on nutrient availability likely requires some hours, explaining the prolonged depression of the insulin secretory response after lunch and dinner on the NoB day.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study has demonstrated that autophagy is suppressed in β-cells during starvation; starvation-induced nascent granule degradation occurs in these starved cells, resulting in a local increase of amino acids, thereby suppressing β-cell autophagy. Starvation-induced nascent granule degradation is positively regulated by inactive protein kinase D1 to suppress autophagy and prevent insulin release under nutrientlimiting conditions 105 . Finally, autophagy promotes glucose uptake and glycolytic flux in Ras-transformed mouse fibroblasts and breast cancer cells; however, it remains unclear whether autophagy similarly promotes intracellular glucose metabolism in oncogenic contexts beyond Ras 106 .…”
Section: Phagophore Autolysosomementioning
confidence: 99%